The EFFECT OF ADVERSE SELECTION AND LOCUS OF CONTROL ON TO THE ESCALATION COMMITMENT TENDENCY IN TAKING DECISION INVESTMENT - SITI RODIAH (Akuntansi & Ekonomika, 2019)
This study aims to examine the effect of adverse selection and locus of control on the tendency of commitment escalation in investment decision making. The sample in this study was 80 accounting students of the University of Muhammadiyah Riau University who were asked to act as managers who were faced with a case related to the escalation of commitments. This research method uses a 2 x 2 experimental design between subjects namely adverse selection (there are adverse selection and without adverse selection) and locus of control (there is locus of control and without locus of control) which is processed using two ways ANOVA analysis techniques with the help of a computer program SPSS 20. The results of this study indicate that adverse selection and locus of control have a significant influence on the escalation of commitments in investment decision making. The results of this study are expected to help managers, especially decision makers, gather more complete information in advance related to their investments to prevent future failures.